2008
DOI: 10.1681/asn.2006101115
|View full text |Cite
|
Sign up to set email alerts
|

Podocytes Contribute to the Formation of Glomerular Crescents

Abstract: The cellular composition of crescents in glomerular disease is controversial. The role of podocytes in crescent formation has been especially difficult to study because podocytes typically lose their characteristic terminally differentiated phenotype under disease conditions, making them difficult to identify. We reasoned that the intermediate filament protein nestin, a marker of progenitor cells that has recently been identified in podocytes, may allow the investigation of podocyte involvement in glomerular c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
87
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(97 citation statements)
references
References 29 publications
7
87
0
3
Order By: Relevance
“…Thus far, podocytes have only been proven to migrate onto Bowman's capsule in the context of an acute inflammatory nephritis such as rapidly progressive GN (RPGN). 31,[45][46][47] In RPGN, podocytes dedifferentiate and migrate via direct adhesions onto Bowman's capsule. There they contribute to the formation of cellular crescents by proliferation together with activated PECs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, podocytes have only been proven to migrate onto Bowman's capsule in the context of an acute inflammatory nephritis such as rapidly progressive GN (RPGN). 31,[45][46][47] In RPGN, podocytes dedifferentiate and migrate via direct adhesions onto Bowman's capsule. There they contribute to the formation of cellular crescents by proliferation together with activated PECs.…”
Section: Discussionmentioning
confidence: 99%
“…Entretanto, ainda há controvérsias a respeito da origem das células hiperplásicas no interior dos glomérulos (Bruggeman & Nelson 2009). Alguns estudos, nos quais marcadores celulares foram utilizados, sugerem que as cé-lulas presentes nas pseudocrescentes na HIVAN e em outras glomerulopatias colapsantes se originem das células epiteliais parietais e não dos podócitos (Nagata et al 1998, Dijkman et al 2006, ao passo que os podócitos também podem contribuir, de certa maneira, para a formação das crescentes glomerulares (Thorner et al 2008, Sistani et al 2012. Os resultados conflitantes caracterizados pela detecção de alguns marcadores específicos de podócitos nas crescentes glomerulares e não detecção de outros poderia ser explicado pela diferenciação dos podócitos e perda de alguns marcadores específicos com a progressão da doença (Sistani et al 2012).…”
Section: Discussionunclassified
“…In the glomerulus, the response to podocyte injury may cause aberrant epithelial cell proliferation, hypercellular lesions formation and Bowman's space obliteration, as seen in collapsing glomerulopathy and in crescentic glomerulonephritis (Albaqumi & Barisoni, 2008;Thorner, et al, 2008). Until now, theories explaining the origin of aberrant epithelial cells in collapsing glomerulopathy and crescentic glomerulonephritis have been controversial.…”
Section: Involvement Of Rsc In Glomerular Disorders and Cancermentioning
confidence: 99%
“…Until now, theories explaining the origin of aberrant epithelial cells in collapsing glomerulopathy and crescentic glomerulonephritis have been controversial. One possibility is that these cells are exclusively of parietal epithelial origin (Thorner et al, 2008 ), while another is that some dedifferentiated podocytes acquire markers of parietal epithelial cells (Moeller et al, 2004). It was recently demonstrated that the majority of cells present in the hyperplastic lesions in collapsing glomerulopathy or crescentic glomerulonephritis exhibits the RSC markers CD133 and CD24, with or without coexpression of podocyte markers .…”
Section: Involvement Of Rsc In Glomerular Disorders and Cancermentioning
confidence: 99%